Сardioprotective agents with biaromatic structure. Part 4. Potassium hERG channels blockers and modulators - G. V. Mokrov (Фармакокинетика и Фармакодинамика)
The hERG subtype potassium channel (Kv11.1) is one of the most important and one of the most studied biological targets for the creation of cardioprotective agents. A large number of both blockers and activators/modulators of the hERG channel have been described with biaromatic structure. Substances with an hERG-mechanism are used primarily for the effective regulation of the action potential duration in the heart tissues and for the control of the QT interval on the electrocardiogram. Among the hERG blockers, the most well-known drug is dofetilide, which is used to maintain sinus rhythm in atrial fibrillation. The review presents all currently known ligands of the hERG channel with a biaromatic structure and the data on their biological properties.